Design, synthesis and antitrypanosomatid activities of 3, 5‐diaryl‐isoxazole analogues based on neolignans veraguensin, grandisin and machilin G. (25th November 2018) - Trefzger, Ozildéia S.; das Neves, Amarith R.; Barbosa, Natália V.; Carvalho, Diego B.; Pereira, Indiara C.; Perdomo, Renata T.; Matos, Maria F. C.; Yoshida, Nidia C.; Kato, Massuo J.; de Albuquerque, Sérgio; Arruda, Carla C. P.; Baroni, Adriano C. M.
Abstract: Using bioisosterism as a medicinal chemistry tool, 16 3, 5‐diaryl‐isoxazole analogues of the tetrahydrofuran neolignans veraguensin, grandisin and machilin G were synthesized via 1, 3‐dipolar cycloaddition reactions, with yields from 43% to 90%. Antitrypanosomatid activities were evaluated against Trypanosoma cruzi, Leishmania ( L .) amazonensis and Leishmania ( V .) braziliensis . All compounds were selective for the Leishmania genus and inactive against T. cruzi . Isoxazole analogues showed a standard activity on both promastigotes of L. amazonensis and L. braziliensis . The most active compounds were15, 16 and19 with IC50 values of 2.0, 3.3 and 9.5 μM against L. amazonensis and IC50 values of 1.2, 2.1 and 6.4 μM on L. braziliensis, respectively. All compounds were noncytotoxic, showing lower cytotoxicity (>250 μM) than pentamidine (78.9 μM). Regarding the structure–activity relationship (SAR), the methylenedioxy group was essential to antileishmanial activity against promastigotes. Replacement of the tetrahydrofuran nucleus by an isoxazole core improved the antileishmanial activity. Abstract : In this work, sixteen 3, 5‐diaryl‐isoxazole analogues based on neolignans veraguensin, grandisin and machilin G were synthesized, and biological activity was evaluated against L. amazonensis, L. braziliensis and T. cruzi .